PENGARUH PERSEPSI GURU SMP TERHADAP MINAT MEMANFAATKAN INTERNET SEBAGAI SUMBER BELAJAR - Elistya Rimawati, Sri Harjanto (STMIK Sinar Nusantara, 2017)
This study is aimed at measuring the teachers’ interest in using internet as the source of study related with the variables perception of information technology, easiness, and risk. The measurement of the variables’ influence is conducted to find out the teachers’ readiness in using internet in their teaching. The samples of the study are the teachers of either public or private junior high schools in Surakarta residence. The data used in this study is the primary data gained by distributing questionaires randomly. The result of the analysis is that the technology perception positively influences the teachers’ interest in using internet as the source of study as much as 0.441 while the easiness perception does the same thing as much as 0.465. On the other hand, the risk perception contributes negative influence of 0.117. The junior high school teachers’ decision to use internet as the source of study is 51.3% influenced by the preception of information technology, the easiness perception, and the risk perception while 48.7% is influenced by other factors excluded in this study. The results of this study can be used as a basis for policy making resource development of teachers.Keywords: information technology, easiness, rick, interest